Phillip Cole: Philosophies of Exclusion, Liberal Political Theory and Immigration.: Edinburgh University Press, Edinburgh 2000 - Muhič-Dizdarevič, Selma (Lidé města, 2005)
A review of the book by Phillip Cole.